2004
DOI: 10.1103/physrevb.70.045409
|View full text |Cite
|
Sign up to set email alerts
|

Effective transition rates for epitaxial growth using fast modulation

Abstract: Thin-film deposition is an industrially important process that is highly dependent on the processing conditions. Most films are grown under constant conditions, but a few studies show that modified properties may be obtained with periodic inputs. However, assessing the effects of modulation experimentally becomes impractical with increasing material complexity. Here we consider periodic conditions in which the period is short relative to the time scales of growth. We analyze a stochastic model of thin-film gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…These prerequisites are met for metal growth by pulsed laser depoa) The authors wish to acknowledge financial supported by the Swiss Bundesamt für Energie (BfE) and Swiss Electric Research (SER) and would like to thank Ulrich Müller (Scanning Probe Microscopy User Laboratory, Empa) for his support. b) Electronic mail: henning.galinski@mat.ethz.ch; http://www.nonmet.mat.ethz.ch sition (PLD) 8,9 , so called laser-MBE, especially in case of the large ratios between the pulse duration (≈ 10−25 ns) and the repetition rate (≈ 1−100 Hz). This circumstance makes PLD ideal for surface-engineering 10 and for studying the fundamentals of metal-on-insulator growth.…”
Section: Pt Thin Films Are Commonly Used As Gate Materials On Metal-inmentioning
confidence: 99%
“…These prerequisites are met for metal growth by pulsed laser depoa) The authors wish to acknowledge financial supported by the Swiss Bundesamt für Energie (BfE) and Swiss Electric Research (SER) and would like to thank Ulrich Müller (Scanning Probe Microscopy User Laboratory, Empa) for his support. b) Electronic mail: henning.galinski@mat.ethz.ch; http://www.nonmet.mat.ethz.ch sition (PLD) 8,9 , so called laser-MBE, especially in case of the large ratios between the pulse duration (≈ 10−25 ns) and the repetition rate (≈ 1−100 Hz). This circumstance makes PLD ideal for surface-engineering 10 and for studying the fundamentals of metal-on-insulator growth.…”
Section: Pt Thin Films Are Commonly Used As Gate Materials On Metal-inmentioning
confidence: 99%
“…For instance, Bellon and Martin [12] suggested that the connection between KMC and absolute times in rejection algorithms is empirical. Many other authors have also pointed out, in some way, the lack of a formal connection between time scales [13].We prove here that rejection-free algorithms are simply a limiting case of a generic class of KMC algorithms, which include the rejection algorithms as well. Simultaneously with the proof, we naturally derive a physical time scale for this generic class of algorithms, which is thus valid for both rejection and rejection-free KMC.…”
mentioning
confidence: 88%
“…For instance, Bellon and Martin [12] suggested that the connection between KMC and absolute times in rejection algorithms is empirical. Many other authors have also pointed out, in some way, the lack of a formal connection between time scales [13].…”
mentioning
confidence: 98%